2016
DOI: 10.1038/npp.2016.69
|View full text |Cite
|
Sign up to set email alerts
|

Morphine-Associated Contextual Cues Induce Structural Plasticity in Hippocampal CA1 Pyramidal Neurons

Abstract: In people with a prior history of opioid misuse, cues associated with previous drug intake can trigger relapse even after years of abstinence. Examining the processes that lead to the formation and maintenance of the memories between cues/context and the opioid may help to discover new therapeutic candidates to treat drug-seeking behavior. The hippocampus is a brain region essential for learning and memory, which has been involved in the mechanisms underlying opioid cravings. The formation of memories and asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 57 publications
2
27
0
Order By: Relevance
“…A recent study found that 1 day withdrawal from repeated morphine administration decreased thin spine density in hippocampal neurons, and this loss of thin spines was associated with increased expression of total RhoA in hippocampal synapses. These effects were present when morphine was administered in a novel environment (conditioning chamber) and not elicited following home cage administered morphine (Fakira et al 2016). This suggests that hippocampal synaptic RhoA induction encodes associations between environmental cues and drug exposure rather than frank morphine reward.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…A recent study found that 1 day withdrawal from repeated morphine administration decreased thin spine density in hippocampal neurons, and this loss of thin spines was associated with increased expression of total RhoA in hippocampal synapses. These effects were present when morphine was administered in a novel environment (conditioning chamber) and not elicited following home cage administered morphine (Fakira et al 2016). This suggests that hippocampal synaptic RhoA induction encodes associations between environmental cues and drug exposure rather than frank morphine reward.…”
Section: Discussionmentioning
confidence: 91%
“…These effects were present when morphine was administered in a novel environment (conditioning chamber) and not elicited following home cage administered morphine (Fakira et al . ). This suggests that hippocampal synaptic RhoA induction encodes associations between environmental cues and drug exposure rather than frank morphine reward.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Following operant water-conditioning, mice underwent a Mor-CPP protocol in the VR environment ( Fig. 2A), modified based on our previous reports Fakira et al, 2016). First, animals underwent a pre-conditioning test in which they ran freely, without reward, to establish a baseline for time spent in each compartment as a measure of any inherent bias individual animals may have for one context over the other.…”
Section: Resultsmentioning
confidence: 99%